Detection of Methylobacterium radiotolerans IMBG290 in potato plants by in situ hybridization - Podolich, O.V.; Kozyrovska, N.O.; Pirttila, A.M. (Інститут молекулярної біології і генетики НАН України, 2009)
A new bacterial strain of pink-pigmented facultative methylotroph (M. radiotolerans IMBG290) which was previously isolated from in vitro grown potato plantlets after their inoculation with Pseudomonas fluorescens IMBG163 was detected in tissues by in situ hybridization method (ISH/FISH). The presence of Methylobacterium rRNA was observed in leaves and stems of potato plantlets, whereas no signal was detected in potato roots. The signal was less abundant in the untreated plants than in the plantlets infected with M. radiotolerans IMBG290.